Antibiotic resistance and One Health: a mapping project - Sabiha Essack (Elsevier, 2018)
Background: The One Health approach is a global strategy that encourages interdisciplinary collaboration on health at the human-animal-environmental interface. Antibiotic resistance is a direct consequence of the selection pressure from antibiotic use in humans, animals, and the environment, requiring a One Health approach towards its containment. The high HIV/AIDS burden and other risk factors for communicable diseases in South Africa results in a high incidence of infectious diseases, engendering extensive antibiotic use and subsequent resistance. Two-thirds of the antimicrobials sold for animal use are used in growth promotion. Although the burden of antibiotic resistance has not been quantified, available evidence indicates that it is escalating in humans, animals, and the environment. There is thus a need to quantify the burden of antibiotic resistance with a view to implementing measures for its containment on biomedical, clinical, sociobehavioural, drug discovery/diagnostics, and policy grounds. Methods: This project delineates the molecular epidemiology, nature, and extent of antibiotic resistance in the One Health context in the uMgungundlovu District in KwaZulu-Natal, South Africa. The aim is to map the fluidity of antibiotic-resistant bacterial clones, antibiotic resistance genes, and their associated mobile genetic elements within and between the human, animal, and environmental health sectors by (1) instituting surveillance programmes on antibiotic use and resistance in human, animal, and environmental health; (2) demonstrating the phenotypic and genotypic mechanisms of antibiotic resistance by sensitivity testing and appropriate screening tests and whole-genome sequencing; and (3) establishing the clonality and genetic determinants of resistance by multi-locus sequence typing and whole-genome sequencing. Findings: This project began in 2017. Isolates have been collected from patients, chicken, water, and soil. The molecular epidemiology of their antibiotic resistance profiles will be determined. The project will (1) provide a proxy surveillance system for antibiotic resistance in humans and food animals and (2) unambiguously give credence to the One Health approach for the containment of antibiotic resistance mooted in the UN General Assembly Political Declaration on Antimicrobial Resistance and by the tripartite alliance of the WHO, the Food and Agriculture Organization, and the World Organisation for Animal Health using a specific conceptual framework. Interpretation: Successful proof of concept will require validation of the conceptual framework in different countries and health systems with different levels of antibiotic resistance and will thus be tested in high-income, middle-income, and low-income countries with different antibiotic resistance burdens. Funding: South African National Research Foundation, South African Medical Research Council.